Prevalence and Risk Factors of Dental Caries in Pediatric Patients: A Clinical Examination-Based Study in a Dental and Oral Hospital - Puji Kurnia; Deli Mona; Mifthahul Khoir; Rossyqoh Durrotul; Surya Arsyiah (HM Publisher, 2025)
Dental caries remains a significant public health concern globally, with a high prevalence among children in Indonesia. The consequences of untreated caries extend beyond oral health, impacting children's overall well-being and quality of life. This study aimed to determine the prevalence and risk factors of dental caries in pediatric patients visiting the Dental and Oral Hospital of Universitas Andalas (RSGM Unand). A cross-sectional study was conducted at RSGM Unand in 2023. A total of 27 pediatric patients, aged 6 to 10 years, were recruited using total sampling. A caries risk assessment was performed using a questionnaire and clinical examination based on the Caries Management by Risk Assessment (CAMBRA) protocol. Data collected included demographic information (age, gender), and caries risk factors identified through the CAMBRA questionnaire and clinical examination. The collected data were analyzed using SPSS software. The study population consisted of 27 children, with a higher proportion of females (59.3%) than males (40.7%). The age distribution showed the highest number of participants were 6 years old (25.9%). The overall prevalence of high caries risk among the studied pediatric patients was 88.9%. A higher percentage of females (87.6%) were categorized as having high caries risk compared to males (90.0%). Among different age groups, children aged 7, 8, and 10 years showed a 100% prevalence of high caries risk. In conclusion, the findings of this study indicated a very high prevalence of caries risk among pediatric patients visiting RSGM Unand. This highlights the urgent need for targeted preventive and management strategies for dental caries in this population. Further research with a larger sample size and the inclusion of a wider range of risk factors is recommended to gain a more comprehensive understanding of the caries burden in this region.